Pengetahuan penata anestesi tentang kompetensi pembimbing klinik keperawatan anestesiologi - Vita Purnamasari (STIKes Surya Global Yogyakarta, 2019)
Clinical Instructor (CI) is one of the components on clinical learning that has an influence on the quality of learning and outcomes. Clinical instructor must know the competencies that must be possessed to be able to achieve the quality of education in accordance with established standards, but there are many clinical Instructor who do not yet know the competencies. Anesthesiology Nursing is one of the new study programs that requires preparation for clinical learning, so important to know the anesthetist's knowledge about competencies that must be possessed as preparation for student clinical practice. The objective of this study is to describe the knowledge of anesthetist nurses about the competencies of clinical instructor in the nursing anesthesiology clinical practice. The study design was descriptive with a qualitative approach, with 4 participants of anesthesiologist nurse at PKU Muhammadiyah Yogyakarta Hospital with in depth interview and snow ball sampling technique. Theresults of this study showed that there were 3 (three) final meanings of clinical instructor competency, namely professional anesthetist competency, effective communication competency, and teaching competency. The conclusion was the anesthetist clinical instructor’s knowledge is in accordance with the competency that the clinical instructor must have, but there is a competency that is not yet known by the anesthetist.